2012
DOI: 10.1007/s10773-012-1412-3
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Superfluid and STU Model

Abstract: In this study we consider STU model as dual picture of superfluid. By using AdS/CFT correspondence we obtain sound modes as a function of black hole charge and temperature. We find that the second sound has linear behavior with charge and fourth sound yields to one by increasing black hole charge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Special case of STU model in 5 dimensions with three electric charges which admits a chemical potential for the U (1) 3 symmetry already used to study QGP which is called STU/QCD correspondence [35][36][37][38][39]. Also D = 5, N = 2 STU model considered as dual picture of superfluid [40]. Motivated by the evidence of superconductive detector for moving magnetic monopoles [21], we would like to investigate effect of magnetic charge on the conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…Special case of STU model in 5 dimensions with three electric charges which admits a chemical potential for the U (1) 3 symmetry already used to study QGP which is called STU/QCD correspondence [35][36][37][38][39]. Also D = 5, N = 2 STU model considered as dual picture of superfluid [40]. Motivated by the evidence of superconductive detector for moving magnetic monopoles [21], we would like to investigate effect of magnetic charge on the conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…Bozza compared the image patterns for several interesting backgrounds and showed that by the separation of the first two relativistic images we can distinguish two different collapsed objects. Further development for other black holes can be found in [26]- [33]. Several interesting studeies are devoted to lensing by naked singularities [34,35], Janis-Newman-Winicour metric [25] and role of scaler field in gravitational lensing [36].…”
Section: Introductionmentioning
confidence: 99%
“…Bozza compared the image patterns for several interesting backgrounds and showed that by the separation of the first two relativistic images, we can distinguish two different collapsed objects. Further studies were developed for other black holes and metrics [15]- [31]. The gravitational lenses are important tools for probing the universe.…”
Section: Introductionmentioning
confidence: 99%